Correlation between morphology and performance of low bandgap oligothiophene:C60 mixed heterojunctions in organic solar cells - Wynands, D; Levichkova, M; Riede, M; Pfeiffer, M; Baeuerle, P; Rentenberger, R; Denner, P; Leo, K (American Institute of Physics, 2010)
We investigate the end-capped oligothiophene derivative α,ω -bis-(dicyanovinylene)-sexithiophene with ethyl side chains (DCV6T) as donor material in heterojunctions with C60. The effect of the substrate temperature on the morphology and related photophysical properties of single DCV6T and mixed DCV6T:C60 layers is investigated. Single layers of DCV6T show crystalline features in UV-visible absorption and x-ray diffraction when grown on a substrate heated to 90 °C. Investigations of DCV6T:C60 mixed layers by atomic force microscopy, UV-visible absorption, and photoluminescence measurements reveal that the elevated substrate temperature induces an increased phase separation between the two materials with larger domain size and higher surface roughness. Based on these observations, we present mixed heterojunction solar cells where the power conversion efficiency (ηPCE) is increased from 1.6% to 3.8% by increasing the substrate temperature from 30 to 90 °C, respectively. © 2010 American Institute of Physics.